Humoral and Cellular Response to Spike of Delta SARS-CoV-2 Variant in Vaccinated Patients With Multiple Sclerosis - Petrone, Linda; Tortorella, Carla; Aiello, Alessandra; Farroni, Chiara; Ruggieri, Serena; Castilletti, Concetta; Meschi, Silvia; Cuzzi, Gilda; Vanini, Valentina; Palmieri, Fabrizio; Prosperini, Luca; Haggiag, Shalom; et al. (Frontiers in Neurology, 2022)
Objectives We assessed vaccination-induced antibody and cellular response against spike from the ancestral strain and from the Delta Severe Acute Respiratory Syndrome CoronaVirus-2 (SARS-CoV-2) variant in patients with Multiple Sclerosis (MS) treated with disease modifying treatments. Methods We enrolled 47 patients with MS and nine controls (“no MS”) having completed the vaccination schedule within 4–6 months from the first dose. The Interferon (IFN)-γ-response to spike peptides derived from the ancestral and the Delta SARS-CoV-2 was measured by enzyme-linked immunoassay (ELISA). Anti-Receptor Binding Domain (RBD) IgG were also evaluated. Results No significant differences were found comparing the IFN-γ-specific immune response between MS and “no MS” subjects to the ancestral (P = 0.62) or Delta peptide pools (P = 0.68). Nevertheless, a reduced IFN-γ-specific response to the ancestral or to the Delta pools was observed in subjects taking fingolimod or cladribine compared to subjects treated with ocrelizumab or IFN-β. The antibody response was significantly reduced in patients with MS compared to “no MS” subjects (P = 0.0452) mainly in patients taking ocrelizumab or fingolimod. Conclusions Cellular responses to Delta SARS-CoV-2 variant remain largely intact in patients with MS. However, the magnitude of these responses depends on the specific therapy.